Nutritional and technological potential of whole unripe Bluggoe and Prata-Anã banana flours (Research, Society and Development, 2020)
The objective of this work was to evaluate the nutritional and technological potential of whole unripe Prata-Anã and Bluggoe flours. Both types of bananas were selected at stage 1 of ripening, including pulp and peel to obtain flour. Determinations of yield, color, chemical composition, resistant starch (RS), antioxidant capacity, total phenolics, tannins, water activity, water absorption, water solubility, oil absorption, and viscosity were carried out. Unripe Prata-Anã and Bluggoe flours presented average yields of 24.2 % and 24.8 %, respectively. The Bluggoe cultivar had a higher pulp content (62.9 %), and Prata-Anã had a higher peel content (41.4 %). A higher RS content and antioxidant capacity for the Prata-Anã cultivar was verified. On the other hand, the Bluggoe cultivar presented a higher fiber content. Prata-Anã WUBF presented higher nutritional and technological application potential. However, both flours require heating during preparation, or pre-cooking, when applied to new food products.